2011
DOI: 10.3390/ijms12074250
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Metals for Cardiovascular Stent Application: Interests and New Opportunities

Abstract: During the last decade, biodegradable metallic stents have been developed and investigated as alternatives for the currently-used permanent cardiovascular stents. Degradable metallic materials could potentially replace corrosion-resistant metals currently used for stent application as it has been shown that the role of stenting is temporary and limited to a period of 6–12 months after implantation during which arterial remodeling and healing occur. Although corrosion is generally considered as a failure in met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
336
0
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 529 publications
(352 citation statements)
references
References 57 publications
0
336
0
16
Order By: Relevance
“…[4][5][6][7][8][9][10] Iron is also an essential element for proper biological functions, mainly for the transfer of oxygen by blood. 13 The recommended daily value of Fe is about 10 mg. 6 Regarding the biocompatibility of iron-based alloys, there are a number of reported results, [14][15][16] but they are often controversial. In order to explain the discrepancies between biocompatibility tests, more in-vitro and in-vivo experiments are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10] Iron is also an essential element for proper biological functions, mainly for the transfer of oxygen by blood. 13 The recommended daily value of Fe is about 10 mg. 6 Regarding the biocompatibility of iron-based alloys, there are a number of reported results, [14][15][16] but they are often controversial. In order to explain the discrepancies between biocompatibility tests, more in-vitro and in-vivo experiments are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate alloying of Mg, Zn and Fe can positively modify their mechanical, corrosion and physical properties, which are important for potential medical applications. In the available literature many alloying elements are proposed for these purposes, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] but in this study Mg-RE (RE = rare earth metals, Gd, Nd, Y), Zn-Mg and Fe-Mn based alloys were selected, because all these alloying systems are generally considered as relatively safe and acceptable for a potential medical use. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated a class of completely watersoluble and fully resorbable silicon-based components (9), shedding light on biodegradable devices (10) with integrated functions that go well beyond those historically offered by resorbable sutures (11), degradable intravascular stents (12,13), and matrices for drug release (14,15). A particular challenge for medical applications is how to externally control such devices and correlate this control with device degradation time, including the electronics and biomaterial support layers.…”
mentioning
confidence: 99%
“…Biodegradable metals corrode and disappear after implantation. This eliminates the need for a subsequent, second surgery to remove the implant or device, as well as lowering the risk of infection and foreign body reaction [8][9][10][11][12]. Mg based implants have experienced good clinical successes in recent years [13][14][15][16][17].…”
Section: Medical Magnesium and Biocorrosionmentioning
confidence: 99%